Alloy, protective layer and component - Stamm, Werner (2021)
Known protective layers having a high Cr-content and a silicone in addition, form brittle phases that embrittle further under the influence of carbon during use. The protective layer according to the invention is composed of 22% to 26% cobalt (Co), 10.5% to 12% aluminum (Al), 0.2% to 0.4% Yttrium (Y) and/or at least one equivalent metal from the group comprising Scandium and the rare earth elements, 15% to 16% chrome (Cr), optionally 0.3% to 1.5% tantal, the remainder nickel (Ni).